La gran velocidad ferroviaria en España: ancho de vía y duplo-red = The high-speed railway in Spain: rail gauge and double-network - Santos y Ganges, Luis (Polígonos. Revista de Geografía, 2002)
La introducción del ancho internacional en España para las nuevas líneas de gran velocidad ferroviaria ha desembocado en el planteamiento gubernamental de disponer de dos futuras redes férreas separativas en el horizonte del año 2010. La cuestión del ancho de vía se resolverá aparentemente optando por una “duplo-red” basada en la especialización y forzando la dualidad entre dos sistemas técnicos, dos velocidades, dos tipos de servicios, dos redes, dos anchos. The introduction of the international track gauge for the new railway high speed lines in Spain has lead to a governmental proposal consisting of having available two distinct railway networks by the year 2010. The question of the track gauge will apparently be solved by opting for a double network based on the specialization, forcing a duality of technical systems involving two speeds, two kinds of services, two networks, two track gauges.